Plant responses to grazer-mediated habitat alterations in tallgrass prairie - Zahner, Anna (Kansas State University, 2015)
The effects of bison activities on forb diversity and cover have been well-established, but less is known about how forb life history is altered by bison-mediated habitat changes. This study had three main objectives: 1) to evaluate the hypothesis that release from aboveground competition with grasses may contribute to the increased cover and diversity of forbs in prairie grazed by bison relative to ungrazed prairie, 2) to determine whether differences in forb reproductive effort between grazed and ungrazed habitats were size-dependent, and 3) to look for evidence of a trade-off between allocation to vegetative and sexual reproduction. The growth, biomass allocation, and sexual reproduction of six common unpalatable perennial species were measured and compared between bison-grazed and ungrazed tallgrass prairie burned at 2-year intervals: Ambrosia psilostachya, Artemisia ludoviciana, Baptisia australis, Psoralidium tenuiflorum, Solidago canadensis, and Vernonia baldwinii. Vegetative reproduction was also measured for B. australis¸ S. canadensis, and V. baldwinii. Light availability, canopy density and height, and percent cover of neighboring plants were measured in each studied individual’s immediate neighborhood and compared between habitats to establish the possibility of differing aboveground competition. Aboveground competition may be lower in bison-grazed habitats, as evidenced by differences in habitat characteristics and plant performance found in this study. In bison-present habitats, sexual reproduction was elevated for all six species and average plant size was greater for all species except A. psilostachya. Vegetative reproduction was not clearly different between habitats for all three species examined. Sexual reproduction increased with size for all species, and the relationship differed significantly between habitats for all species except A. psilostachya. Allocation to vegetative reproduction was not generally related to aboveground biomass, nor was there a clear trade-off between allocation to vegetative and sexual reproduction. The results of this study provide evidence that release from aboveground competition with grasses promotes the growth and sexual reproduction of the studied species of forb, and that differences in sexual reproduction are not entirely size-dependent. Patterns in allocation to vegetative reproduction were less clear and were not clearly tied to sexual reproductive allocation.
Keywords: Resource allocation; Tallgrass prairie; Forb; Grazing; Life history; Competition; Ecology (0329); Plant Biology (0309)